Development and psychometric validation of the Nausea/Vomiting Symptom Assessment patient-reported outcome (PRO) instrument for adults with secondary hyperparathyroidism - Colleen A. McHorney; Mark E. Bensink; Laurie B. Burke; Vasily Belozeroff; Chad Gwaltney (SpringerOpen, 2018)
Abstract Background We developed the Nausea/Vomiting Symptom Assessment (NVSA©) patient-reported outcome (PRO) instrument to capture patients' experience with nausea and vomiting while on calcimimetic therapy to treat secondary hyperparathyroidism (SHPT) related to end-stage kidney disease. This report summarizes the content validity and psychometric validation of the NVSA©. Methods The two NVSA© items were drafted by two health outcomes researchers, one medical development lead, and one regulatory lead: it yields three scores: the number of days of vomiting or nausea per week, the number of vomiting episodes per week, and the mean severity of nausea. An eight-week prospective observational study was conducted at ten dialysis centers in the U.S. with 91 subjects. Criterion measures included in the study were the Functional Living Index-Emesis, Kidney Disease Quality of Life Instrument, EQ-5D-5 L, Static Patient Global Assessment, and Patient Global Rating of Change. Analyses included assessment of score distributions, convergent and known-groups validity, test-retest reliability, ability to detect change, and thresholds for meaningful change. Results Qualitative interviews verified that the NVSA© captures relevant aspects of nausea and vomiting. Patients understood the NVSA© instructions, items, and response scales. Correlations between the NVSA© and related and unrelated measures indicated strong convergent and discriminant validity, respectively. Mean differences between externally-defined vomiting/nausea groups supported known-groups validity. The scores were stable in subjects who reported no change on the Patient Global Rating of Change indicating sufficient test-retest reliability. The no-change group had mean differences and effect sizes close to zero; mean differences were mostly positive for a worsening group and mostly negative for the improvement group with predominantly medium or large effect sizes. Preliminary thresholds for meaningful worsening were 0.90 days for number of days of vomiting or nausea per week, 1.20 for number of episodes of vomiting per week, and 0.40 for mean severity of nausea. Conclusions The NVSA© instrument demonstrated content validity, convergent and known-groups validity, test-retest reliability, and the ability to detect change. Preliminary thresholds for minimally important change should be further refined with additional interventional research. The NVSA© may be used to support study endpoints in clinical trials comparing the nausea/vomiting profile of novel SHPT therapies.